Green synthesis and characterization of silver nanoparticles based on Helianthemum lippii L. extract and evaluation of their biological activities - LAIB Ibtissam (جامعة الوادي university of eloued, 2024)
In this context, The main objective of this work is to green synthesis of AgNPs from H.lippii aqueous extract and to evaluate the biological effects of H.lippii plant and silver nanoparticles in vitro and as well as in vivo in order to look into their potential therapeutic effects against the physiological and biochemical changes brought on by sub-chronic exposure to cadmium chloride in rats. For this purpose, quantitative, qualitative, and extraction bioactive compounds standard procedures were applied. While identification and quantification of individual phenolic compounds were performed by HPLC analysis. On the other hand, has been of AgNPs green synthesis and characterization by different methods (UV, FTIR, XRD, and SEM). In addition, in vitro activities Evaluation has been done via antioxidant, anti-inflammatory, Hemolytic, and antibacterial activities, Meanwhile, Spectrophotometric, Voltammetric studies of the binding interaction of AgNPs with deoxyribonucleic acid and bovine serum albumin under similar condition. In regards to studying in vivo, 35 Wistar male rats were divided into seven groups ( 5 rats in each): Control, H.lippii, CdCl2, CdCl2+H.lippii, AgNPs, CdCl2+AgNPs, and CdCl2+H.lippii+AgNPs. CdCl2 (50mg/Kg) was added in drinking water for 35 day. The therapeutic systems were received intragastrically for H.lippii (100 mg/kg b.w) and AgNPs were supplemented intraperitoneally at 0.1mg/kg for the last 15 days. Some biochemical, hematological, oxidative stress markers and histopathology were observed The phytochemical analysis revealed the presence of most of the phenolic compounds, Further, H. lippii had high levels of total phenolics (183.12±2.84mg GA eq/g dry Ex) and flavonoid contents (72.00±1.03 mg QE/mg Ex), as well as saponins (82.2± 33.00 mg DO eq/g dry Ex), and of tannins (Total hydrolyzable tannin; 2.818±0.138mgTA eq/g dry Ex, Condensed tannin; (5.88±1.58 mg Ca eq/g dry Ex) and anthocyanins (4.256±0.590 mg C-3-GE/g dry Ex). HPLC analysis identified six phenolic compounds in high concentration, mainly gallic acid and chlorogenic acid. According to, the absorption peak at 428 nm characterized the synthesized silver nanoparticles, the crystalline nature of AgNP was confirmed by XRD patterns, and SEM analysis revealed that the majority of the nanoparticles were spherical in shape. While investigations using FT-IR technique confirmed the presence of many functional groups that are involved in covering and reducing AgNPs. In addition, H.lippii and AgNPs demonstrated strong efficiency as antioxidant, and anti-inflammatory, while providing moderate protection for red blood cells. On the other hand, they showed good antibacterial activity against six types of selected bacteria. Moreover, the results show that there is a spontaneous interaction between AgNPs and DNA as well as BSA via electrostatic interactions, translated by parameters K and ΔG. On the other hand, according to the results obtained in vivo, there was a decrease in the body weight gain. An increase in the relative weight of the liver, kidneys, heart and brain, with a decrease in the absolute and relative weight of the testicle. Moreover, the findings in cadmium chloride-treated rats induced significant changes in hematological and biochemical, hormonal parameters, hepatic enzyme markers, and renal function compared to the control group. These changes were accompanied by a decrease in antioxidant defense (GSH, SOD, and CAT) and an increase in MDA levels. The data clearly showed the deterioration of the structure of the studied tissues in comparison with the control group, including severe deterioration of liver and kidney cells, while testicular tissues showed severe necrosis. However, the treatment with H.lippii and/or AgNPs mitigated most of toxic effects and the restored all previous variable parameters. Finally, this study demonstrated the promising biological activity of H.lippii and AgNPs, Meanwhile, it is worth noting the strong therapeutic potential of H.lippii and AgNPs against cadmium chlorideinduced toxicity in rats, which opens new avenues for the use of phytotherapy and nanotherapy and enhances their application in approaches medical.
Applied Biochemistry
Keywords: Helianthemum lippii; silver nanoparticles; green synthesis; biological activities; cadmium chloride; Wistar rats.